Human breast milk‐derived exosomes through inhibiting AT II cell apoptosis to prevent bronchopulmonary dysplasia in rat lung. Issue 15 (14th July 2022) - Zhou, Yahui; Liu, Yiwen; Xu, Gen; Liu, Lingjie; Li, Huimin; Li, Yubai; Yin, Jing; Wang, Xingyun; Yu, Zhangbin
Abstract: Human breast milk (HBM) effectively prevents and cures neonatal bronchopulmonary dysplasia (BPD). Exosomes are abundant in breast milk, but the function of HBM‐derived exosomes (HBM‐Exo) in BPD is still unclear. This study was to investigate the role and mechanism of HBM‐Exo in BPD. Overall lung tissue photography and H&E staining showed that HBM‐Exo improved the lung tissue structure collapse, alveolar structure disorder, alveolar septum width, alveolar number reduction and other injuries caused by high oxygen exposure. Immunohistochemical results showed that HBM‐Exo improved the inhibition of cell proliferation and increased apoptosis caused by hyperoxia. qPCR and Western blot results also showed that HBM‐Exo improved the expression of Type II alveolar epithelium (AT II) surface marker SPC. In vivo study, CCK8 and flow cytometry showed that HBM‐Exo improved the proliferation inhibition and apoptosis of AT II cells induced by hyperoxia, qPCR and immunofluorescence also showed that HBM‐Exo improved the down‐regulation of SPC. Further RNA‐Seq results in AT II cells showed that a total of 88 genes were significantly different between the hyperoxia and HBM‐Exo with hyperoxia groups, including 24 up‐regulated genes and 64 down‐regulated genes. KEGG pathway analysis showed the enrichment of IL‐17 signalling pathway was the most significant. Further rescue experiments showed that HBM‐Exo improved AT II cell damage induced by hyperoxia through inhibiting downstream of IL‐17 signalling pathway (FADD), which may be an important mechanism of HBM‐Exo in the prevention and treatment of BPD. This study may provide new approach in the treatment of BPD.